O-mannosylation and N-glycosylation: Two coordinated mechanisms regulating the tumour suppressor functions of E-cadherin in cancer - Carvalho, S (2016)
Dysregulation of tumor suppressor protein E-cadherin is an early molecular event in cancer. O-mannosylation profile of E-cadherin is a newly-described posttranslational modification crucial for its adhesive functions in homeostasis. However, the role of O-mannosyl glycans in E-cadherin-mediated cell adhesion in cancer and their interplay with N-glycans remains largely unknown. We herein demonstrated that human gastric carcinomas exhibiting a non-functional E-cadherin display a reduced expression of O-mannosyl glycans concomitantly with increased modification with branched complex N-glycans. Accordingly, overexpression of MGAT5-mediated branched N-glycans both in gastric cancer cells and transgenic mice models led to a significant decrease of O-mannosyl glycans attached to E-cadherin that was associated with impairment of its tumour suppressive functions. Importantly, overexpression of protein O-mannosyltransferase 2 (POMT2) induced a reduced expression of branched N-glycans which led to a protective effect of E-cadherin biological functions. Overall, our results reveal a newly identified mechanism of (dys)regulation of E-cadherin that occur through the interplay between O-mannosylation and N-glycosylation pathway.